Analytical Hierarchy Process of human resources performance: perceptions perspective - Adya Hermawati (Jurnal Inovasi Ekonomi, 2021)
This research aims to recommend a policy model as the base in making strategies to improve the performance and sustainable competitiveness of Micro, Small & Medium Enterprises (MSMEs) in the tourism sector. Variables used by this research are role, actor, and priority. These variables are measured by weighing them against human resource performance. Method of research involves quantitative and qualitative approaches. The sampling technique is purposive sampling. The research results comprise three findings, which all refer to the results of assessment done by the employees of MSMEs regarding the relationship between variables and MSMEs performance. First, transglobal leadership is the most needed criterion to improve performance. The second is that Community is the actor whose role is most needed to improve performance. Finally, the third is productivity and professionality as a priority.